2018
DOI: 10.1002/eap.1787
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity of indigenous and western scientific approaches for monitoring forest state

Abstract: Cross-cultural environmental monitoring systems inform on a broad suite of indicators relevant to both scientific and local communities. In this study, we used forest-plot-based survey measures developed by western scientists and a set of community-based survey indicators developed by Māori, the indigenous people of New Zealand (NZ), to compare the current state of two ecologically congruent forests (Whirinaki and Ruatāhuna), as they related to a historic Ruatāhuna forest state (Baseline; 1955-1975) in NZ. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…Because foundation species characteristically define the systems they create, nonspecialists and citizen-scientists should be engaged in identifying and articulating the cultural value of foundation species and other ecologically important ones (e.g., Ens et al., 2015, Costanza et al., 2017). Numerous studies have found that members of traditional cultures and other nonspecialists can identify individual species, their functional values, and ecosystem characteristics that are well correlated with ecological indicator species and quantitative metrics used by ecologists to assess ecosystem states (e.g., Zhao et al., 2016, Charnley et al., 2017, Done et al., 2017, Lyver et al., 2018). People from all backgrounds and with a wide range of abilities now have access to tools for identifying species and contributing to growing databases on species occurrences and traits (Farnsworth et al., 2013).…”
Section: Pro-active Identification Of Foundation Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because foundation species characteristically define the systems they create, nonspecialists and citizen-scientists should be engaged in identifying and articulating the cultural value of foundation species and other ecologically important ones (e.g., Ens et al., 2015, Costanza et al., 2017). Numerous studies have found that members of traditional cultures and other nonspecialists can identify individual species, their functional values, and ecosystem characteristics that are well correlated with ecological indicator species and quantitative metrics used by ecologists to assess ecosystem states (e.g., Zhao et al., 2016, Charnley et al., 2017, Done et al., 2017, Lyver et al., 2018). People from all backgrounds and with a wide range of abilities now have access to tools for identifying species and contributing to growing databases on species occurrences and traits (Farnsworth et al., 2013).…”
Section: Pro-active Identification Of Foundation Speciesmentioning
confidence: 99%
“…People from all backgrounds and with a wide range of abilities now have access to tools for identifying species and contributing to growing databases on species occurrences and traits (Farnsworth et al., 2013). Individual and cultural memories also may add substantial historical insights about ecological changes that are otherwise unavailable (Lyver et al., 2018). Synthesizing all these information streams with available scientific data could lead to more rapid progress in identifying candidate foundation species.…”
Section: Pro-active Identification Of Foundation Speciesmentioning
confidence: 99%
“…Such translations carry inherent risk “of losing some of its meaning, or because it may be embedded in place and taking it out of context would render it spiritless” (Castleden et al 2017 c ). There is also recognition of inter‐generational (i.e., traditional) knowledge transfer within communities to prevent ecological memory loss (Lyver et al 2018). Indigenous scholarship on knowledge systems typically embraces the spiritual/sacred, the emotional, and both Human/Human and Human/non‐Human relationships.…”
Section: Indigenous Scholarship Regarding Knowledge Systemsmentioning
confidence: 99%
“…Indigenous scholarship on meaningful and respectful knowledge system interactions often highlights the importance of such guiding principles, captured by Levac et al (2018) as Reciprocity, Relationality, Reflexivity, Respect, Reverence, Responsivity, and Responsibility, with an emphasis on each, varying in different relational contexts. Underlying some of these Indigenous approaches to knowledge system interactions is the idea of the “co‐production of knowledge” (Boillat and Berkes 2013, Lyver et al 2018, Adelle et al 2020), or seeing the interaction as a “co‐learning journey” (Castleden et al 2017 a , 2017 b , Wehi et al 2019 a ), whereas other Indigenous approaches focus on shifting or addressing power imbalances. Several scholars have strongly emphasized that Indigenous de‐colonizing approaches to knowledge system interactions require recognizing Indigenous Nations as treaty partners rather than simply as “stakeholders” (Zanotti and Palomino‐Schalscha 2016, Reo et al 2017, Ruru et al 2017).…”
Section: Indigenous Scholarship Regarding Knowledge Systemsmentioning
confidence: 99%
“…For example, The Waikato River Authority (Waikato River Authority 2018) and the Rangitāiki River Forum (Bay of Plenty Regional Council 2018) are both formally mandated co-governance arrangements established as part of Treaty settlements. Shifting towards a holistic and equal consideration of all values will require learning from and applying Mātauranga Māori (Māori knowledge) and applying tikanga and kawa (protocols and practices) to capture cultural values (Lyver et al 2017(Lyver et al , 2018. It must also be recognised that much of our farming landscape will require targeted and sustained efforts to reintroduce lost biodiversity to recreate biodiverse, culturally relevant and resilient landscapes (Meurk & Swaffield 2000), that result in biodiversity persistence, increased resilience of ecosystems, people and communities, and maintains sustainable productive use of land.…”
Section: First-steps Towards a Solutionmentioning
confidence: 99%